Intravascular Papillary Endothelial Hyperplasia of the Jejunum as a Cause of Obscure‐Overt Gastrointestinal Bleeding. Issue 1 (2017) - Gotfried, Jonathan; Dorta, Raul Berio; Maranki, Jennifer
ABSTRACT : N/A: Intravascular papillary endothelial hyperplasia (IPEH), or Masson's tumor, is a rare, benign vascular lesion characterized by reactive endothelial proliferation with venous stasis and thrombus. Lesions typically arise in vascular regions of the head and neck or extremities, but involvement of other organ systems has been reported. Clinically, IPEH mimics other benign lesions (hemangiomas) and malignant neoplasms (angiosarcoma) depending on the affected site. Diagnosis is essential because local excision of certain IPEH subtypes is curative. IPEH in the gastrointestinal tract is rare with few reported cases. We present a case of obscure‐overt gastrointestinal bleeding from IPEH of the jejunum.